2020
DOI: 10.21203/rs.3.rs-58810/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circular RNA expression profiles and features in NAFLD mice: a study using RNA-seq data

Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is primarily characterized by the hepatic cholesterol accumulation. Circular RNA (circRNA), one of noncoding RNA, involves in many liver diseases progression. However, no recent studies on circRNA expression profiles in NAFLD have been reported previously. Methods: A NAFLD mouse model was constructed by providing high-fat diet (HFD) for 32 weeks. The circRNAs expression profile in normal mice and NAFLD mice were determined using high-output RNA sequencing me… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Supplementary Table 2: the summary of fatty liver disease-related lncRNAs [15,. Supplementary Table 3: the summary of fatty liver diseaserelated circRNAs [88][89][90][91][92][93][94][95][96][97][98][99]. (Supplementary Materials)…”
Section: Abbreviationsmentioning
confidence: 99%
“…Supplementary Table 2: the summary of fatty liver disease-related lncRNAs [15,. Supplementary Table 3: the summary of fatty liver diseaserelated circRNAs [88][89][90][91][92][93][94][95][96][97][98][99]. (Supplementary Materials)…”
Section: Abbreviationsmentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD) is a broadspectrum term used to generalize non-alcoholic fatty liver simple steatosis and non-alcoholic steatohepatitis (NASH). Simple steatosis is the initial stage within the spectrum of NAFLD, which progresses to NASH and increases the risk of developing fibrosis, cirrhosis, and hepatocellular carcinoma [1,2]. NAFLD has affected 10 to 48 percent of the general population in different countries of the world [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Li M et al found that circ PTK2 can regulate microglial activation and hippocampal neuronal apoptosis in sepsis 9 ; Jiang Z et al found that circ PTK2 can promote colorectal cancer cell proliferation, migration, invasion and chemoresistance 10 ; and Yang Z et al indicated that circ PTK2 can contribute to laryngeal squamous cell carcinoma via the miR‐1278/YAP1 axis 11 . In addition, Yuan X et al demonstrated that circ PTK2 was downregulated in NAFLD mice, suggesting that circ PTK2 might act as an inhibitor in NAFLD 12 . However, the detailed function of circ PTK2 in NAFLD remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…11 In addition, Yuan X et al demonstrated that circ PTK2 was downregulated in NAFLD mice, suggesting that circ PTK2 might act as an inhibitor in NAFLD. 12 However, the detailed function of circ PTK2 in NAFLD remains largely unknown. MicroRNAs (miRNAs) are endogenous RNAs with regulatory functions in cellular processes.…”
mentioning
confidence: 99%